Comparison of the Effectiveness of Schema Therapy and Emotionally Focused Therapy (EFT) on Increasing Empathy and Reducing Symptoms of Marital Depression in Couples - Siavoshi , Hatam; Kordestani, Davood (Mental Health and Lifestyle Journal, 2025)
The present study was conducted to compare the effectiveness of schema therapy and Emotionally Focused Therapy (EFT) on empathy and symptoms of marital depression in couples. The research method was quasi-experimental with a pretest-posttest and follow-up design including two experimental groups and one control group. The sample of the present study consisted of 60 couples from the city of Hamadan who were selected through purposive sampling and assigned to three groups of 20 participants each. Subsequently, two groups were randomly assigned as experimental groups and one group as the control group. Standardized questionnaires were used in this study. After considering the assumptions of statistical analysis, the data were analyzed using repeated measures analysis of variance and Bonferroni post hoc test. The findings indicated that there was a significant difference between the schema therapy group and the Emotionally Focused Therapy (EFT) group compared with the control group in the variables of empathy and depressive symptoms (p < .05). Furthermore, a significant difference was observed between the schema therapy experimental group and the Emotionally Focused Therapy experimental group based on the mean scores of the variables in the posttest and follow-up stages (p < .05). The results demonstrated that schema therapy was more effective than Emotionally Focused Therapy in increasing empathy, whereas Emotionally Focused Therapy was more effective than schema therapy in reducing symptoms of depression.